Optimization of coagulation-flocculation process for colour removal in purification of paint industry effluent using novel seed of Spondias mombin Linn - Ifeoma MaryJane Iloamaeke; Samuel Ifechukwu Atune; Ugomma Chibuzo Onyeije; Theresa Uzoma Onuegbu (Desalination and Water Treatment, 2025)
In response to growing environmental concerns over industrial wastewater, this study investigates the use of a novel plant-based coagulant derived from Spondias mombin Linn (SML) seeds for treating paint industry effluent. The coagulant’s colour removal efficiency was assessed using a jar test and optimized through a Box-Behnken Design (BBD) matrix. Physicochemical analysis of the raw effluent showed high pollutant levels, including acidity (134 mg/L), hardness (294 mg/L), sulphate (120 mg/L), TSS (156.30 mg/L), BOD (129 mg/L), and dark red colour. Heavy metals such as lead (0.245 mg/L), iron (0.968 mg/L), and chromium (0.07 mg/L) exceeded NIS limits. Characterization of SML before and after treatment using SEM, FTIR, and XRD revealed decreased surface porosity, bonding of functional groups to contaminants, and a shift from crystalline to amorphous structure, respectively. The BBD-generated second-order polynomial model (R² = 0.9688, p < 0.05) confirmed significant interactions among coagulant dosage, pH, and settling time. Optimal conditions 0.4 g/L dosage, pH 10, and 30 min settling time—achieved a colour removal efficiency of 82.291 % ±2.244. These findings demonstrate that SML seed is a promising, sustainable, and low-cost alternative to conventional coagulants for effective treatment of paint industry wastewater.